Constructing ethnic identification variables of Malay, Chinese and Iban - Ernest Cyril, de Run (The ICFAI Journal of Marketing Management, 2012)
This paper sets out to measure ethnic identification variables in a Malaysian context. Seven most widely accepted constructs of ethnic identity, language, friendship networks, religious affiliation, participation in clubs and organizations, endogamy, food preference and traditional celebrations were translated into nine constructs. Data collected was analyzed using exploratory factor analysis on three ethnic groups, Malay, Chinese and Iban in Malaysia. The findings indicate that “my language” and “my friends” can measure ethnic identification strength, with a caveat for religion for Malays.